Build international biorepository capacity - Jocelyn P., Colella; Bernard Risky, Agwanda; Faisal Ali, Anwarali Khan; John, Bates; Carlos A., Carrión Bonilla; Noé U., de la Sancha; Jonathan L., Dunnum; Adam W., Ferguson; Stephen E., Greiman; Prince Kaleme, Kiswele; Enrique P., Lessa; Pamela, Soltis; et al. (AAAS, 2020)
In their Perspective “Rigorous wildlife disease surveillance” (10 July, p. 145), M. Watsa et al. underscore the value of One Health approaches to stimulate integration across currently siloed efforts in zoonotic research and mitigation. To achieve comprehensive decentralized pathogen surveillance, there is an urgent need to develop environmental and biodiversity infrastructure in biodiverse countries experiencing high rates of habitat conversion, wildlife trafficking, and human-wildlife interactions.